A cost-benefit analysis of farmer based seed production for common bean in Kenya - Katungi, Enid M.; Karanja, D.; Wozemba, D.; Mutuoki, T.; Rubyogo, Jean-Claude (African Crop Science Society, 2011)
Community based informal seed production has recently gained popularity as an alternative to the formal seed sector of disseminating new crop varieties including the common bean. This is because farmer produced seed is readily available and is more affordable by most farmers than certified seed. This study examined the profitability of farmer based common bean seed production in Kenya. The study used data collected from farmers and one seed company participating in seed multiplication. The principal finding was that farmer based common bean seed production was a profitable enterprise and was less sensitive to price fluctuations. Compared to certified common bean seed production, net profit margins were five times higher for certified common bean seed than for farmer based common bean seed production. With the current varieties, profitability depends on access to irrigation and good agronomy.